'Summer of Sport': the development of a 6-week programme in increasing physical activity to improve public health outcomes. (December 2019) - Abdin, S.; Welch, R.K.; Fieldhouse, A.J.; Baker, A.L.; McBurney, S.L.; Reed, A.; Martino, O.I.; Denley, J.O.; Byron-Daniel, J.Z.
Abstract: Objectives: A population-based physical activity (PA) programme was implemented to increase PA levels and encourage individuals to join the local council leisure facility. Study design: This is a cross-sectional design. Methods: The 6-week programme Summer of Sport (SOS) involved a total of 487 individuals registered for PA sessions. The sessions were held at three local council leisure facilities included badminton, swimming, table tennis, squash and group cycle. The programme was assessed using a survey based on the Theory of Planned Behaviour. Individuals were asked for their current fitness levels, whether the programme encouraged them to be more active and for their intentions to join the leisure centre after the programme. Results: Of the 487 who originally registered for the programme, there were 161 users of SOS, with 112 not already members of the leisure facility. After the programme, 83% considered themselves already being active, with 78% stating that they partook in at least 30 min of exercise, 3 times per week. Although a large proportion of individuals were already physically active, 78% stated that taking part encouraged them to become more active. More than half suggested that they would not join the leisure facility, 30% said that they had joined after the programme and 17% stated their intention to join. Many individuals highlighted that the programme provided an opportunity to be active with their family. Conclusions: Public health teams should work with partner organisations to embed robust processes for measuring outcomes that impact on population health. Highlights: Physical activity is generally low during the summer periods. A 6-week programme was developed to increase physical activity across a population. Physical activity sessions including swimming and table tennis were held at local leisure facilities. Individuals were asked for current fitness levels, whether the programme encouraged activity and for their intentions to join the leisure centre. Public health teams should work with partner organisations to embed robust processes for measuring population health outcomes.